Intangible Property as a Tool for Analyzing the Relationships Between Government and Private Enterprise - Carlin, Edward A. (Quarterly Journal of Economics, 1953)
I. Introduction, 112. — II. Historical analysis of relationship of government to private enterprise, 113. — III. The concept of competition as a tool for analysis, 114. — IV. Criteria of a conceptual tool, 116. — V. Emphasis on the relationship itself a clue to concept of property rights, 117. — VI. Intangible property as a conceptual tool, 118.